IMPACT STRENGTH TEST ON ADDITION OF AGAVE SISALANA FIBER AND E-GLASS FIBER IN ACRYLIC RESIN DENTAL PLATE REPAIR : UJI KEKUATAN IMPAK TERHADAP PENAMBAHAN AGAVE SISALANA FIBER DAN E-GLASS FIBER PADA REPARASI PLAT GIGI TIRUAN RESIN AKRILIK - Ni Kadek Sugianitri; Suhendra (Interdental Jurnal Kedokteran Gigi (IJKG), 2021)
Introduction: Acrylic resin is the most common material for the denture base because acrylic resin has good esthetics, ease of processing, reparability and inexpensive. A disadvantage of acrylic resin is that it is easily to be cracked. One of the ways to resolve this problem is by adding the agave sisalana fiber and E-glass fiber. The purpose of this study was to find out the effect after addition agave sisalana fiber and E-glass fiber on impact strength of an acrylic resin denture plate reparation. Material and Method: The experiment involved twenty seven plates of heat-cured acrylic with the dimensions of 55x 10 x 10 mm with the 26 x 5 x 4 mm for the cavity to measure, each measurement divided into three groups, with nine samples for each groups. The first group as a control group (without fiber), the second group as a group with agave sisalana fiber addition, the third group as a group with e-glass fiber addition. All plates were soaked in distillation water for one day at 37oC. Plates were tested for impact strength using the charpy method. All data obtained was analyzed with one-way ANOVA followed by LSD (Least Significant Difference) with p<0,05. Result and Discussion: The result showed that the influences of impact strength between without fiber with agave sisalana fiber and E-glass fiber addition on acrylic denture reparation. Acrylic denture reparation in both fibers with concentration 3,3%, agave sisalana fiber has the highest impact strength rather than e-glass fiber. Conclusion: The conclusion of this study is that there is an increase in impact strength with agave sisalana fiber and E-glass fiber addition on acrylic denture reparation and agave sisalana fiber has the highest impact strength.